THE RELATIONSHIP BETWEEN COMMUNITY SUPPORT AND ADHERENCE TO ANTENATAL CARE VISITS AMONG PREGNANT WOMEN - Siti Maisaroh (Yayasan Education and Social Center, 2025)
Pregnancy is one of the important periods that requires special attention to maintain the health of the mother and fetus. One of the efforts made to monitor health during pregnancy is through antenatal care (ANC) visits. The compliance of pregnant women in conducting ANC visits is influenced by various factors, one of which is community support. Objective: This study aims to determine the relationship between community support and compliance with antenatal care (ANC) visits in pregnant women. Methods: This study used the Systematic Literature Review (SLR) method. Articles are obtained through Google Scholar and national and international journals relevant to the research topic. The selection of articles was carried out based on inclusion and exclusion criteria, then analyzed according to the research objectives. Results: The results of the literature review showed that the support of husbands, families, health cadres, and the community had a significant relationship with compliance with ANC visits in pregnant women. The support provided is in the form of emotional, informational, motivational, and mentoring support that helps increase the awareness of pregnant women to carry out routine pregnancy checkups. In addition, pregnant women's classes and community-based health education also help increase the use of maternal health services. Conclusion: Community support has an important role in improving compliance with ANC visits in pregnant women so that it can support maternal and fetal health during pregnancy.